THE IMPORTANCE OF THE APPLICATION ON INFORMATION AND COMMUNICATION TECHNOLOGIES IN THE PROMOTION OF TOURIST POTENTIALS NAD CULTURAL HERITAGE OF BOSNIA AND HERZEGOVINA (Heritage, 2022)
Information and communication technologies (ICT) have already entered many pores of modern society and without it, is difficult to imagine the life of modern man. In this paper, we will point out only он one segment of the application of ICT, and that is in the tourism sector and in the promotion of cultural heritage. Tourism can be a significant generator of income for a country, and it also has the potential to employ a large number of people. The application of ICT and especially the Internet, has greatly changed the way in which information is presented to users and the way in which users access information and how travel is organized.The application of ICT leads to the development of new marketing tools based on the digital platform, such as websites and portals whose content is adapted to computers and mobile phones, as well as increasingly represented advertising through social networks and search engines.
Keywords: информационо-комуникационе технологије, културна башина, туризам